(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article provides a brief historical overview of Mozambican theater, exploring its trajectory, development, current moment, and future perspectives. It addresses the cultural effervescence of Maputo, the capital of Mozambique, with the aim of increasing the visibility of the city’s theater and dance productions and generating primary references on the subject. It offers an overview of the local artistic scene and seeks to fill the gap in studies and references regarding these cultural manifestations. The research, conducted as part of the author’s doctoral work, was based on interviews with local artists and personal archives, given the scarcity of bibliographic materials on the topic.